Occupational Characteristics of Semiconductor Workers with Cancer and Rare Diseases Registered with a Workers' Compensation Program in Korea - Dong-Uk Park; Sangjun Choi; Seunghee Lee; Dong-Hee Koh; Hyoung-Ryoul Kim; Kyong-Hui Lee; Jihoon Park (Elsevier, 2019)
Background: The aim of this study was to describe the types of diseases that developed in semiconductor workers who have registered with the Korea Workers' Compensation and Welfare Service (KWCWS) and to identify potential common occupational characteristics by the type of claimed disease. Methods: A total of 55 semiconductor workers with cancer or rare diseases who claimed to the KWCWS were compared based on their work characteristics and types of claimed diseases. Leukemia, non-Hodgkin lymphoma, and aplastic anemia were grouped into lymphohematopoietic (LHP) disorder. Results: Leukemia (n = 14) and breast cancer (n = 10) were the most common complaints, followed by brain cancer (n = 6), aplastic anemia (n = 6), and non-Hodgkin lymphoma (n = 4). LHP disorders (n = 24) accounted for 43%. Sixty percent (n = 33) of registered workers (n = 55) were found to have been employed before 2000. Seventy-six percent (n = 42) of registered workers and 79% (n = 19) among the registered workers with LHP (n = 24) were found to be diagnosed at a relatively young age, ≤40 years. A total of 18 workers among the registered semiconductor workers were finally determined to deserve compensation for occupational disease by either the KWCWS (n = 10) or the administrative court (n = 8). Eleven fabrication workers who were compensated responded as having handled wafers smaller than eight inches in size. Eight among the 18 workers compensated (44 %) were found to have ever worked at etching operations. Conclusion: The distribution of cancer and rare diseases among registered semiconductor workers was closely related to the manufacturing era before 2005, ≤8 inches of wafer size handled, exposure to clean rooms of fabrication and chip assembly operations, and etching operations. Keywords: Chip assembly, Etching, Fabrication, Leukemia, Semiconductor operation